A 13‐year longitudinal study of the impact of air pollution on cognition. (31st December 2021) - Wu, Jing; Grande, Giulia; Stafoggia, Massimo; Ljungman, Petter; Laukka, Erika J; Bellander, Tom; Rizzuto, Debora
Abstract: Background: Accumulation of evidence has raised concern regarding the harmful effect of air pollution on cognitive function, but results are inconclusive. We aimed to investigate whether long‐term exposure to air pollutants may have an adverse effect on cognitive function in older adults residing in an urban area. Method: Data for this study were obtained from the Swedish National Study on Aging and Care in Kungsholmen. Cognitive impairment, no dementia (CIND) was assessed by a comprehensive neuropsychological battery. We assessed long‐term residential concentrations of particulate matters (PM2.5 and PM10 ) and nitrogen oxides (NOx) with land use regression. Long‐term air pollution was included as a time‐varying variable. Hazard ratio (HR) and 95% confidence interval (CI) were estimated with Cox proportional hazards. Departures from linearity were presented by fitting models with cubic splines with 3 knots at fixed percentiles (10th, 50th, 90th) of its distribution. We further explored the effect of long‐term air pollution exposure on the progression of CIND cases assessed at baseline to dementia incidence, using Cox hazard models. Result: Among 2499 participants, 351 individuals developed CIND during the follow‐up. A 1‐μg/m 3 increment in PM2.5 exposure was associated with a 63% increased risk of CIND incidence (HR=1.63, 95%CI: 1.44‐1.86). Weaker associations were found for PM10 (HR=1.06, 95%CI: 1.01‐1.11) and NOx (HR=1.01, 95%CI: 1.00‐1.02). Among those CIND cases at baseline (N=607), 118 participants developed dementia during follow‐ups. We observed an increased hazard of dementia for a 1‐μg/m 3 increment in PM2.5 exposure in individuals with prevalent CIND at baseline, although non‐statistically significant (HR=1.24, 95%CI: 0.88‐1.74). Conclusion: We found suggestive evidence of an association between ambient air pollutants and incidence of CIND and its progression to dementia in older adults. Further research should focus more on the underlying mechanisms.